Valuable Bioproducts Production of Haematococcus lacustris Integrated with Phycoremediation of Liquid Digestate of POME (LDP) Under a Continuous Three-Stage Cultivation System - Asiandu, Angga Puja; Budiman, Arief; Nugroho, Andhika Puspito; Suyono, Eko Agus (HAYATI Journal of Biosciences, 2026)
Integrating astaxanthin production by using Haematococcus lacustris with the LDP phycoremediation provides multiple benefits. However, as a highly sensitive organism, the cultivation needs to be regulated, such as selecting the most favorable media, regulating light intensity, adjusting LDP conentration, and evaluating the effect of NaCl on astaxanthin biosynthesis. In this study, we developed a new cultivation method, three-stage continuous cultivation system, by regulating the light intensity at each stage of microalgae growth. Based on the evaluation, the ideal medium was MES-volvox. The favorable light intensity for the adaptation phase was 600 lux, with the best LDP concentration of 3.75% and NaCl 1 g/L. The desirable light intensity in the three-stage cultivation system was 600 lux (days 0-6), 1,200 lux (days 6-16), and 3,500 lux (days 16-30). This system produced density, biomass, and astaxanthin content up to 91.54 × 104 cells/mL, 1 g/L, 0.83 g/L, respectively. Remarkably, the enrichment of NaCl did not reduce the density, carbohydrate, protein, or pigment content. Therefore, it may serve as a safe astaxanthin-enhancing stressor in the cultivation of this microalgae.